REAKSI PASAR MODAL DARI DAMPAK PERISTIWA BOM PLAZA SARINAH TERHADAP ABNORMAL RETURN PERUSAHAAN LQ 45 YANG TERDAFTAR DI BEI - Ika Yustina Rahmawati; Tiara Pandansari (Universitas Muhammadiyah Surakarta, 2016)
The purpose of this study was to analyze the reaction of the capital market from the impact of the bombing in Jakarta Sarinah Plaza, which will be indicated by the presence or absence of abnormal return. the sample used is the stock of LQ 45, this study is event study so that the observation period will see the reaction on before, during and after the event. In this study period used was H-5 (before the event), H0 (current events) and H + 5 (after the event). Sources of data obtained from yahoo finance, sahamok.com and IDX. The data used in this research is secondary data, such as the closing price of shares has been adjusted (adjusted closing price) and the closing price of IHSG. Data in the form of daily stock price. The data was then analyzed using analytical methods paired sample t-test. The results showed that when viewed from the average abnormal return (AAR) did not show any difference, only the H+3 and H+4 which shows the differences in AAR and signaled their reaction to the stock market to these events that affect market participants in make decisions. Keywords: Average Abnormal Return (AAR), event study, Bomb Sarinah Plaza.